2007
DOI: 10.1016/j.marenvres.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Nodularin induces oxidative stress in the Baltic Sea brown alga Fucus vesiculosus (Phaeophyceae)

Abstract: In the Baltic Sea regular, intensive cyanobacterial blooms rich in the cyanobacterium Nodularia spumigena occur during the summer season. N. spumigena is known to produce the cyclic pentapeptide nodularin (NOD) in high concentrations. Marine macroalgae, together with sea-grass meadows, are an extremely important habitat for life in the sea. In addition to this, the decaying macroalgae substantially contribute to the substrate for the microbial loop in coastal food webs. Uptake of nodularin into the brown macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…In fish, NOD accumulation can range from 0.1-2230 mg kg À1 dry weight, depending on the organs analysed and the technique used. In contrast, primary producers such as Cladophora fracta and Fucus vesiculosus accumulate the lowest amounts of the toxin (Sipia¨et al, 2001(Sipia¨et al, , 2002(Sipia¨et al, , 2007Karjalainen et al, 2005;Strogyloudi et al, 2006;Mazur-Marzec et al, 2007;Pflugmacher et al, 2007). Despite the low NOD concentrations reported for the lower trophic levels, it has been suggested that zooplankton may act as a toxin vector, increasing its range (Karjalainen et al, 2005).…”
Section: Nodularin Accumulation and Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, NOD accumulation can range from 0.1-2230 mg kg À1 dry weight, depending on the organs analysed and the technique used. In contrast, primary producers such as Cladophora fracta and Fucus vesiculosus accumulate the lowest amounts of the toxin (Sipia¨et al, 2001(Sipia¨et al, , 2002(Sipia¨et al, , 2007Karjalainen et al, 2005;Strogyloudi et al, 2006;Mazur-Marzec et al, 2007;Pflugmacher et al, 2007). Despite the low NOD concentrations reported for the lower trophic levels, it has been suggested that zooplankton may act as a toxin vector, increasing its range (Karjalainen et al, 2005).…”
Section: Nodularin Accumulation and Transfermentioning
confidence: 99%
“…Nevertheless, the high degree of depuration and/or detoxication processes across trophic levels observed in both field and experimental studies could explain the tolerance of some zooplankton species to Nodularia (Karjalainen et al, 2007). Indeed, data accumulated over recent years suggest that NOD is transformed and degraded to less toxic compounds at each trophic level (Strogyloudi et al, 2006;Karjalainen et al, 2007;MazurMarzec et al, 2007;Pflugmacher et al, 2007;Sipia¨et al, 2007).…”
Section: Nodularin Accumulation and Transfermentioning
confidence: 99%
“…Nodularin is a cyclic pentapeptide, hepatotoxin and tumor promoter (Ohta et al, 1994). Exposure to nodularin induces oxidative stress in mussels (Davies et al, 2005;Kankaanpää et al, 2007), fish (Vuorinen et al, 2009) and marine macroalga Fucus vesiculosus (Pflugmacher et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is defined as a negative reaction due to exposure of molecules, cells, or tissues to free radical oxidants, generally called reactive oxygen species (ROS), occurring in excess levels (Li et al, 2005a). Oxidative stress is often a consequence of cyanobacterial toxicity in mammals (BouaÏcha and Maatouk, 2004;Lankoff et al, 2002), marine plants (Pflugmacher et al, 2007) and fish (Jos et al, 2005;Prieto et al, 2006). Antioxidant enzymes prevent cellular damages caused by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%